Variation in Gemological Characteristics in Tsavorites with Different Tones from East Africa - Yuanmeng Ma; Ying Guo (Crystals, 2022)
In this paper, the influencing factors of the color and the gemological changes of tsavorites with different tones from East Africa were studied. The gemological characteristics of 35 different green tones in tsavorites were collected based on the results of color measurement, X-ray fluorescence, ultraviolet–visible, infrared and Raman spectroscopy. V and Cr are responsible for the samples’ color: with the increase of vanadium content, lightness L* and chroma C* decreased while hue h° increased, and the hue tends to blueish green. The color of tsavorite is related significantly to the absorption bands at about 430 nm and 605 nm through the UV-VIS spectrum. Under long-wave ultraviolet light, the samples show inert or red fluorescence. The G, H, and I peaks of the infrared spectrum are shifted towards the long-wave direction with the reduction of the V content. The peaks at 275 nm, 412 nm and 545 nm on the Raman spectrum tend to move towards the direction of decreasing wavelength with the increase of V content.